2022
DOI: 10.3390/microorganisms10071455
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Diversity during Spontaneous Fermentations and Oenological Characterisation of Indigenous Saccharomyces cerevisiae for Potential as Wine Starter Cultures

Abstract: Diversity of regional yeast can be influenced by geography, grape cultivars and the use of SO2, but at single vineyard scale in China, the impact of these factors on yeast population, particularly Saccharomyces cerevisiae, is not well studied. Here, we characterised yeast species and dynamics during spontaneous fermentations with/without SO2 using eight typical grape cultivars from Yuma vineyard in Ningxia wine region of China. Results show that distribution and abundance of yeast species varied by grape varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 56 publications
0
20
0
Order By: Relevance
“…The analysis of volatile compounds was performed using gas chromatography–mass spectrometry (GC–MS), in combination with headspace solid‐phase microextraction (HS‐SPME), as previously described (Chen et al ., 2022), with slight modifications. Briefly, 5.0 mL of a sample was placed in a 15 mL glass vial containing 1.0 g NaCl and 10 μL internal standards (4‐methyl‐2‐pentanol, 20 mg/L) and equilibrated at 40 °C with 400 rpm agitation for 30 min.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The analysis of volatile compounds was performed using gas chromatography–mass spectrometry (GC–MS), in combination with headspace solid‐phase microextraction (HS‐SPME), as previously described (Chen et al ., 2022), with slight modifications. Briefly, 5.0 mL of a sample was placed in a 15 mL glass vial containing 1.0 g NaCl and 10 μL internal standards (4‐methyl‐2‐pentanol, 20 mg/L) and equilibrated at 40 °C with 400 rpm agitation for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…The concentrations of the compounds were calculated using calibration curves following Chen et al . (2022), and details of the standards are shown in Table S1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In detail, wines fermented with autochthonous yeasts were characterized by the presence of noticeable esters such as isoamyl acetate (banana scent) and ethyl octanoate (apple, pear, and peach aroma). Consistently, Chen et al [ 74 ] demonstrated how the use of indigenous S. cerevisiae yeasts, as opposed to industrial starters, can lead to an increase in the aromatic composition regarding the production of esters like ethyl hexanoate or ethyl acetate, thus conferring an aromatic distinctive imprint linked to the geographical location [ 74 ].…”
Section: Contribution Of Selected Yeasts To Emerging Winemaking Demandsmentioning
confidence: 99%
“…Nevertheless, this fermentation method has relied heavily on the raw materials with differently initial microbiota, presenting challenges in ensuring consistency of the final product quality across different batches. Selecting key fermentative species have been regarded as the crux of the transformation from spontaneous fermentation to commercially controlled fermentation, aiming to guarantee the fermentation finish without the interference of polluted species ( Chen et al, 2022 ). Taken together, investigation of microbial diversity with geographical feature in spontaneous fermentation are of high importance for revealing how distinct chemical compositions are formed, and for the selection of expectative starters that can substitute spontaneous fermentation, especially for apricot wines (which has not been proven to date).…”
Section: Introductionmentioning
confidence: 99%